2021
DOI: 10.1016/j.hroo.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan versus angiotensin inhibitors and arrhythmia endpoints in heart failure with reduced ejection fraction

Abstract: BACKGROUND Angiotensin receptor-neprilysin inhibitor (ARNI) therapy has been associated with improved survival for patients with symptomatic heart failure and reduced ejection fraction (HFrEF).OBJECTIVES We performed a meta-analysis of arrhythmia endpoints from studies comparing ARNI with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) for patients with HFrEF to assess for incremental benefit. METHODSWe searched PubMed, Embase, and ClinicalTrials.gov. Baseline study cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…There was no significant difference in terms of arrhythmia endpoints (both atrial and ventricular arrhythmias) between sacubitril-valsartan and control group patients. Previous studies assessing these endpoints have also reported no difference between these groups [64,65]. Here also, the number of trials assessing these outcomes is limited and requires further large-scale trials to provide conclusive evidence on arrhythmia endpoints.…”
Section: Discussionmentioning
confidence: 89%
“…There was no significant difference in terms of arrhythmia endpoints (both atrial and ventricular arrhythmias) between sacubitril-valsartan and control group patients. Previous studies assessing these endpoints have also reported no difference between these groups [64,65]. Here also, the number of trials assessing these outcomes is limited and requires further large-scale trials to provide conclusive evidence on arrhythmia endpoints.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to previous meta-analysis, no significant association between sacubitril/valsartan and the occurrence of atrial arrhythmias, including AF, was observed. Another meta-analysis by Fernandes et al concluded that ARNI therapy was associated with lower SCD events and ventricular arrhythmias compared with control in HFrEF ( 8 ). However, the finding was underpowered limited to the included observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analyses on the similar topic have been published ( 8 , 9 ). The meta-analysis by Fernandes et al found that ARNI therapy was associated with a reduction in SCD and ventricular arrhythmias compared with control in HF with reduced ejection fraction (HFrEF) ( 8 ). However, the role of sacubitril/valsartan in HF with preserved ejection fraction (HFpEF) remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis by Pozzi et al [ 62 ] demonstrated a significant reduction in the burden of VA and ICD shock when comparing ARNi to ACEi/ARB therapy. Fernandes et al [ 63 ] reported a significant reduction in SCD, VA, and appropriate ICD therapy with ARNi. Major studies and meta-analyses regarding the effect of ARNi on VA and SCD are summarized in Table 1 .…”
Section: Angiotensin Receptor–neprilysin Inhibitormentioning
confidence: 99%